2021
DOI: 10.3389/fonc.2021.787198
|View full text |Cite
|
Sign up to set email alerts
|

The Surgeon’s Proficiency Affected Survival Outcomes of Minimally Invasive Surgery for Early-Stage Cervical Cancer: A Retrospective Study of 851 Patients

Abstract: PurposeTo compare the clinical outcomes of patients with early-stage cervical cancer who underwent minimally invasive surgery (MIS) by surgeons in different phases and evaluate whether the proficiency of surgeons affects the survival outcomes.Materials and MethodsA total of 851 patients with early-stage cervical cancer who underwent radical hysterectomy between January 2008 and June 2018 (every year from January to June) at a tertiary hospital were retrospectively analyzed. We categorized patients into four ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
2
3
0
Order By: Relevance
“…Thus, our findings indicate a positive effect of surgical proficiency in MIS for early-stage cervical cancer. These results are in concordance with those of previously reported studies 15 - 18 , 22 .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Thus, our findings indicate a positive effect of surgical proficiency in MIS for early-stage cervical cancer. These results are in concordance with those of previously reported studies 15 - 18 , 22 .…”
Section: Discussionsupporting
confidence: 94%
“…Several studies have reported the correlation between surgical proficiency and clinical outcomes 15 - 18 . However, evidence regarding the association of surgical proficiency with survival outcomes in MIS remains insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that when stratified by surgical phases, the OS and DFS of the MIS group in the phase 1 group were significantly lower compared to the other phases and compared to the open surgery group after adjusting for age, BMI, FIGO stage, histologic subtype, and grade. Interestingly, when looking specifically at patients in the phase 1 group, the OS and DFS were in line with those of the LACC trial [61].…”
Section: The Effect Of Surgical Expertise/learning Curvesupporting
confidence: 69%
“…This factor was not considered in the LACC trial. Moreover, the proficiency of surgeons has also been shown to influence the survival outcomes of MIS (30). The surgeon criterion for LRH in the LACC trial was only 10 cases, which is definitely insufficient.…”
Section: Discussionmentioning
confidence: 99%